The dark side of the mining “boom” in Colombia (2017)
This book seeks to offer a general approaching to breaches to human rights and the adverse effects on the environment resulting from the open economic policies implemented by the last Colombian Government’s between 2002 and 2014 for the extraction of gold and coal in the departments of Antioquia, Cesar, La Guajira and Tolima.